Plant protease inhibitors induced oxidative and nutritional stress in helicoverpa armigera unveils multifaceted survival strategies: a lipidomic and metabolomic view - Dewangan, Veena; Gupta, Sonu Kumar; Deshpande, Neha; Lomate, Purushottam R.; Kumar, Yashwant; Giri, Ashok P. (ACS Omega, 2026)
Plant protease inhibitors impede insect growth and development by targeting digestive proteases. In response, insects adapt by modulating protease expression; however, their survival may not rely solely on digestive plasticity and likely involves broader physiological adjustments. To investigate this, we performed an integrated lipidomic and metabolomic analysis of Helicoverpa armigera larvae fed on the recombinant Capsicum annuum protease inhibitor (rCanPI-7), a four-domain inhibitor with potent activity against insect trypsins and chymotrypsins. The results revealed extensive metabolic reprogramming in H. armigera under rCanPI-7-induced stress, prominently affecting amino acid, glutathione, and pyrimidine metabolic pathways with distinct shifts in alanine, arginine, histidine, and branched-chain amino acid metabolism. Suppression of glycolysis and the tricarboxylic acid cycle indicated reduced primary energy metabolism, while oxidative stress was evident from glutathione depletion, lipid peroxidation, and ceramide accumulation, which are hallmarks of mitochondrial dysfunction. To offset this metabolic imbalance, H. armigera mobilized triglycerides and amino acids as alternative energy sources. Reinforcing antioxidant defenses, membrane remodeling, and activating apoptotic and neuromodulatory pathways plausibly aided in restoring cellular homeostasis. Collectively, these findings reveal a tightly coordinated physiological tug of war in H. armigera, where the detrimental effects of rCanPI-7-induced oxidative and nutritional stress were countered through compensatory metabolic, structural, and signaling adjustments. This study provides the first lipidomic insight into this pest species, offering a deeper understanding of its biochemical resilience and potential metabolic vulnerabilities for targeted biopesticide strategies.